A conceptual model of consumer attitudes towards SMS advertising - Dix, Steve; Jamieson, Kyle (School of Marketing, Curtin Business School, 2009)
This paper presents the theoretical applications relevant to a study on the drivers of consumer acceptance of SMS advertising. This paper applies common underlying theories such as the Technology Acceptance Model and Diffusion of Innovation Theory to the field of SMS advertising. Common marketing concepts and theories are also applied to each of the proposed constructs within the study, Utility, Context, Sacrifice, Control, Trust and Attitudes to Advertising in General. This paper then summarises the study in the form of a conceptual framework, presenting a model and proposed hypotheses to be tested.